Detection of lung cancer in bronchial brushing specimens by FISH. (September 2012) - Voss, Jesse S; Kipp, Benjamin R; Halling, Kevin C
Evaluation of : Liu YZ, Wang Z, Fang LL et al . A potential probe set of fluorescence in situ hybridization for detection of lung cancer in bronchial brushing specimens. J. Cancer Res. Clin. Oncol. 138(9), 1541–1549 (2012). Bronchial brushing cytology specimens collected during flexible bronchoscopy are an important part of the diagnostic workup of patients with indeterminate pulmonary nodules. Unfortunately, false-negative diagnoses are not uncommon when sampling peripheral nodules, especially small nodules <2 cm in diameter. A number of studies have evaluated different FISH probe sets to increase the detection rate of lung cancer on bronchial brushings and washings. Most studies have shown that FISH with routine cytology increases the sensitivity of lung cancer detection over routine cytology alone, while maintaining high specificity. In this article, the authors review a recently published three-probe FISH assay for the detection of lung cancer in bronchial brushing specimens.